Role of procalcitonin in predicting newborn hospital-acquired sepsis: a case-control study - Javeed Iqbal Bhat; Shaib Mohd Bhat; Zubair Mushtaq Tramboo; Bashir Ahmad Charoo (SpringerOpen, 2023)
Abstract Background Neonatal sepsis is a leading cause of newborn mortality in the developing world. Most of the newborn babies admitted to a neonatal ICU for different reasons acquire hospital-acquired infections. Early and optimal management is pivotal for successful outcomes. However, most of the places lack advanced automated culture facilities. Procalcitonin could potentially be used for early diagnosis of such infection. Objective To study the diagnostic role of serum procalcitonin in newborn hospital-acquired sepsis. Materials and methods A case-control study was conducted in a tertiary care hospital in northern India. Results Culture-positive nosocomial sepsis group consisted of 59 patients and the control group of 41 patients. Gram-negative organisms were the most commonly isolated organisms (91.5%). The baseline median and interquartile range (IQR) serum PCT of the study population was 0.3 (0.18-.44) ng/ml. The median (IQR) serum PCT values at the time of clinical deterioration in the nosocomial sepsis and the sepsis-like illness groups are 4 (6.5) ng/ml and 1.2 (1.6) ng/ml, respectively (p = 000). The area under the ROC curve for the prediction of bacterial infection for PCT was 0.864. On the ROC curve, the PCT level that combined the greatest sensitivity and comparatively good specificity was 1.95 ng/ml, with a sensitivity of 88%, and specificity of 79%. Conclusion We conclude that serum procalcitonin is a reliable marker for the diagnosis of neonatal nosocomial sepsis.